2018
DOI: 10.19080/artoaj.2018.17.556022
|View full text |Cite
|
Sign up to set email alerts
|

Feed Resource Availability and their Nutrient Contribution for livestock Evaluated Using Feed Assessment Tool (FEAST) in Burie Zuria District, North Western Ethiopia

Abstract: Constraints of livestock production, major livestock feed resources and their nutrient contribution (% of respondents) and intervention options in three agro-ecologies of Burie Zuria district, north western Ethiopia, were assessed from data collected between January 2017 and February 2018. Agro-ecologies, kebeles and households (HHs) were selected using multi-stage sampling techniques. A single-visit multi subject formal survey was conducted. The district was stratified in to high, mid and low altitudes and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…This might be the low human population density residing in the area. In agreement, better landholding of farmers in low altitudes might be expansion of farmland without restriction by clearing of forest and low population density [14].…”
Section: Landholding and Utilizationmentioning
confidence: 96%
See 3 more Smart Citations
“…This might be the low human population density residing in the area. In agreement, better landholding of farmers in low altitudes might be expansion of farmland without restriction by clearing of forest and low population density [14].…”
Section: Landholding and Utilizationmentioning
confidence: 96%
“…This was due to oxen were directly related with crop farming activities. In agreement, oxen are highly demanded for cultivation and other farm activities in Burie Zuria District, North Western Ethiopia [14]. Male calves are grown for traction purpose in South Western Ethiopia [17].…”
Section: Cattle Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, annual average milk yield per cow per 305-days lactation obtainable was less than 2000 kg from pure dairy breeds, 1000 from cross breeds and 500 kg from indigenous cows in Eastern Africa [5,[10][11][12]. Studies have also described high milk variability during the dry season among SDFs compared with their large scale counterparts [13], and suggested that in the smallholder dairy farming context, seasonally determined milk fluctuation is significantly determined by dairy cattle nutritional status [14]. High milk fluctuations in SDFs arise because most farmers, firstly, depend on rainfall for feed production and rarely make provisions for adequate green feed and fodder preservation for the dry season.…”
Section: Introductionmentioning
confidence: 99%